Early Selection for Smut Resistance in Sugarcane Using Pathogen Proliferation and Changes in Physiological and Biochemical Indices - Su, Yachun; Wang, Zhuqing; Xu, Liping; Peng, Qiong; Liu, Feng; Li, Zhu; Que, Youxiong (Frontiers in Plant Science, 2016)
Sugarcane smut disease, caused by Sporisorium scitamineum, significantly decreases yield and use of resistant cultivars is the most cost-effective measure for disease control. Current field testing methods for identification of smut resistance are time-consuming and hindered by environmental variability. Our goal was to develop an efficient and reliable resistance identification technique that is rapid, performed in a controlled environment, and stable. Nine sugarcane cultivars with different phenotypic resistance levels were selected. TaqMan quantitative real-time polymerase chain reaction (qRT-PCR) analysis was performed to measure copy number changes of smut pathogen in sugarcane buds at 0–7 d after needle puncture inoculation. There was a positive correlation between time after inoculation and the amount of smut pathogen in the sugarcane bud. This reached a peak value on 7 d, and the copy number of S. scitamineum decreased in the following order: YZ03-258, FN40, YZ01-1413, GT02-467, ROC22, YT96-86, YZ03-103, FN39, LC05-136. After smut pathogen inoculation, differences in the physiological and biochemical indices of the nine cultivars were observed. Peroxidase (POD), ascorbate peroxidase (APX), catalase (CAT), superoxide dismutase (SOD), β-1,3-glucanase, and malondialdehyde (MDA) were grouped into three main components, and the cumulative contribution rate was 80.177%, revealing that these are useful physiological and biochemical indicators of smut resistance. Subordinate function analysis indicated that the levels of smut resistance of the nine genotypes were (high to low): YZ03-258, FN40, YZ01-1413, GT02-467, ROC22, YZ03-103, YT96-86, FN39, LC05-136, which is similar to the results from copy number determination of smut pathogens. The results suggest that after artificial needle inoculation, rapid identification of physiological resistance to sugarcane smut was achieved based on copy number increases in the sugarcane smut pathogen and the physiological and biochemical changes in sugarcane bud during the early phase of infection.